Developing an Integrated Model of Authentic Assessment in Islamic Religious Education (PAI): Cognitive, Affective, and Psychomotor Dimensions - Khoirur Rozikin; Yusuf Suffandi; Bachrurrosyadi Amrullah; Haniatul Khoiroh (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This article examines an integrated model of authentic assessment for Islamic Religious Education (PAI) that holistically combines the cognitive, affective, and psychomotor domains of student learning. Current PAI assessment practice remains dominated by conventional written testing that captures cognitive mastery alone, leaving affective and psychomotor achievement largely undocumented. Using a qualitative library-research design with content analysis of relevant primary and secondary sources, this study finds that authentic assessment in PAI is firmly grounded in the Islamic educational tradition, reflected in the concepts of al-hisab (accountability), al-imtihan (examination), and al-musyahadah (observation). Building on this foundation, the study proposes an integrated model comprising four components: (1) Islamic Portfolio Assessment, (2) Religious Project Assessment, (3) Self- and Peer Assessment grounded in muhasabah, and (4) Continuous Religious Behavioral Observation. The four components are designed as a single, mutually reinforcing system aligned with the Merdeka Curriculum's emphasis on formative, competency- and character-based assessment. The findings are intended to guide PAI teachers, madrasah administrators, and policymakers in developing assessment systems that are more authentic, meaningful, and equitable across Islamic educational institutions